Allelic and genotype frequencies of major CYP2B6 polymorphisms in the Pakistani population. Issue 3 (18th February 2021) - Ahmed, Sagheer; Khan, Saeed; Janjua, Kholood; Imran, Imran; Khan, Arif Ullah
Abstract: Background: Cytochrome P450 (CYP2B6) is an important enzyme that metabolizes about 3.0% of therapeutic drugs. Drugs metabolized mainly by CYP2B6 include artemisinin, bupropion, cyclophosphamide, efavirenz, ketamine, and methadone. The genetic polymorphisms in the CYP2B6 gene have earlier been studied in many populations, but the data are lacking for the Pakistani population. This research study aimed to determine the frequencies of the three of the most important variant alleles and genotypes of the CYP2B6 gene in the Pakistani population. Methods: Blood was withdrawn from healthy volunteers after taking informed consent. DNA was extracted using commercial kits, and allelic and genotype frequencies were determined after PCR amplification followed by restriction fragment length polymorphism (RFLP) and gel electrophoresis. Results: Our results show a minor allele frequency of 33.8% for CYP2B6*6, 25.8% for CYP2B6*4, 6.5% for CYP2B6*3, whereas wild‐type genotype frequency was 48.57% for CYP2B6*6, 59.79% for CYP2B6*4, and 90.20% for CYP2B6*3 . A significant interethnic variation was also observed. Conclusions: Our results suggest that the frequency of poor metabolizers of CYP2B6, especially *6 variant, is significant enough in the Pakistani population to be given an important consideration when drugs metabolized by this enzyme are prescribed. Abstract : This study shows that a significant portion of the Pakistani population possesses at least one abnormal activity allele of the CYP2B6 gene, especially the frequency of the CYP2B6*6 variant is significant enough in the Pakistani population to be given an important consideration when drugs metabolized by this enzyme are prescribed.